A CMOS frequency generation module for 60-GHz applications - 周春元 张雷 王洪瑞 钱鹤 (Journal of semiconductors, 2012)
A frequency generation module for 60-GHz transceivers and phased array systems is presented in this paper. It is composed of a divide-by-2 current mode logic divider （CML） and a doubler in push-push configuration. Benefiting from the CML structure and push-push configuration, the proposed frequency generation module has a wide operating frequency range to cover process, voltage, and temperature variation. It is implemented in a 90-nm CMOS process, and occupies a chip area of 0.64 × 0.65 mm^2 including pads. The measurement results show that the designed frequency generation module functions properly with input frequency over 15 GHz to 25 GHz. The whole chip dissipates 12.1 mW from a 1.2-V supply excluding the output buffers.